Weight gain of premature neonates related to the type of milk - Rhuama Karenina Costa Silva; Nilba Lima de Souza; Richardson Augusto Rosendo da Silva; João Batista da Silva; Naira Beatriz Pinto Raulino Ladisláo; Samara Isabela Maia de Oliveira (Universidade Federal de Goias, 2014)
The objective of the present study was to compare the weight gain of premature neonates fed with maternal milk from its own mother and those fed with maternal milk from a human donor milk bank (HDMB). A quantitative, descriptive, comparative and prospective study conducted in a Teaching Maternity Unit; including 39 charts of premature neonates between July and October 2011. The data were analyzed using SPSS 20.0 statistical software. The greatest weight gain was found among premature babies with extremely low birth weight using blended milk (exclusive mother's maternal milk + HDMB); followed by neonates with very low birth weight using exclusively their own mother's milk. The study indicated that mother's maternal milk is the most nutritious feeding option and propitiates greater weight gain among low-weight neonates. doi: 10.5216/ree.v16i3.21748.